2018
DOI: 10.1016/j.mayocp.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Function on the Pharmacokinetics, Pharmacodynamics, Efficacy, and Safety of Non–Vitamin K Antagonist Oral Anticoagulants

Abstract: With the growing integration of nonevitamin K antagonist oral anticoagulants (NOACs) into clinical practice, questions have arisen regarding their use in special populations, including groups that may have been underrepresented in clinical trials. Patients with renal impairment, particularly in the lower echelons of renal function, are one such group. In an effort to elucidate the current evidence regarding the use of NOACs in patients with renal impairment, a systematic assessment of the literature was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 94 publications
1
9
0
1
Order By: Relevance
“…Of note, hyperfiltration or augmented/enhanced renal clearance is a condition characterized by creatinine clearance (CrCl) > 130 mL/min and is typical in critically ill patients. 28,29 In this context, real-world data 30 suggest that dabigatran is less efficacious than warfarin in patients with CrCl > 90 mL/min; rivaroxaban shows a trend toward higher relative rates of stroke and systemic embolism 31 in subjects with CrCl > 95 mL/min; and apixaban carries a higher hazard ratio (HR) 32,33 for first ischemic stroke when CrCl > 80 mL/min. In addition, a box warning from the US Food and Drug Administration and an alert from the European Medicines Agency have been provided regarding use of edoxaban in patients with CrCl >95 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, hyperfiltration or augmented/enhanced renal clearance is a condition characterized by creatinine clearance (CrCl) > 130 mL/min and is typical in critically ill patients. 28,29 In this context, real-world data 30 suggest that dabigatran is less efficacious than warfarin in patients with CrCl > 90 mL/min; rivaroxaban shows a trend toward higher relative rates of stroke and systemic embolism 31 in subjects with CrCl > 95 mL/min; and apixaban carries a higher hazard ratio (HR) 32,33 for first ischemic stroke when CrCl > 80 mL/min. In addition, a box warning from the US Food and Drug Administration and an alert from the European Medicines Agency have been provided regarding use of edoxaban in patients with CrCl >95 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Apixaban is excreted about 25% through kidneys and the reduced dose in the renal impaired patients was found to be effective as compared to all NOACs. Apixaban showed superiority over warfarin in the prevention of stroke, embolism, bleeding, and even mortality rate has decreased the pharmacokinetics of all NOACs, which is affected by the activity of pglycoprotein and cytochrome P450 3A4 [10,39].…”
Section: Renal Insufficiencymentioning
confidence: 99%
“…Non-valvular atrial fibrillation (NVAF) and chronic kidney disease (CKD) are frequently associated with each other [1]. In the pivotal randomized controlled trials (RCTs) that lead to the approval of direct oral anticoagulants (DOACs) for stroke prevention in patients with NVAF, patients with an estimated creatinine clearance (CrCl) <25-30 ml/min [1][2][3] were excluded, and the overall frequency of patients with moderate renal impairment (CrCl <50 ml/min) was about 19% [4]. This applies also to the Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF) [5], in which 21% of patients had a CrCl <50 ml/min.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, among the latter group, all patients who were randomized to rivaroxaban in ROCKET-AF received the lower 15 mg once daily dose [5,6]. Based on pharmacokinetic rationales, this reduced dose was also subsequently approved for use in clinical practice in NVAF patients with severe renal impairment (CrCl range 15 to 30 ml/min) [1,3,7]. Interestingly, previous studies indicated a potential benefit of anticoagulation with DOACs versus vitamin K antagonist (VKA) for renal outcomes including a slower decline of renal function over time and reduced development of CKD stage 5 [8,9].…”
Section: Introductionmentioning
confidence: 99%